2021
DOI: 10.3389/fpsyt.2021.706559
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Socioeconomic Status and Depressive Symptoms of Young Adults: Mediating Role of Childhood Trauma

Abstract: Background: Studies have shown that low childhood socioeconomic status (SES) is associated with a high prevalence of depressive symptoms. Childhood trauma, as a potential consequence of low SES, may play an important part, but the mediation effect of childhood trauma remains to be elucidated.Methods: A cross-sectional survey was conducted among 1,807 university students. The MacArthur Scale of Subjective Social Economic Status—Youth Version, Childhood Trauma Questionnaire, and Beck Depression Inventory were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The role of environmental factors in the pathogenesis of MDD has attracted greater attention from physicians and researchers ( Foster et al, 2017 ; O’Mahony et al, 2017 ). Several studies have shown that people who have experience of physical abuse (PA) or emotional abuse (EA) are more likely to suffer from depression ( Biedermann et al, 2021 ; Husain et al, 2021 ), and the severity of symptom is strongly associated with childhood maltreatment ( Whitaker et al, 2021 ; Yang et al, 2021 ; Rep et al, 2022 ). According to a study, the effects of childhood maltreatment could last for decades and are strongly associated with the onset of mental disorders at an older age ( Macpherson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of environmental factors in the pathogenesis of MDD has attracted greater attention from physicians and researchers ( Foster et al, 2017 ; O’Mahony et al, 2017 ). Several studies have shown that people who have experience of physical abuse (PA) or emotional abuse (EA) are more likely to suffer from depression ( Biedermann et al, 2021 ; Husain et al, 2021 ), and the severity of symptom is strongly associated with childhood maltreatment ( Whitaker et al, 2021 ; Yang et al, 2021 ; Rep et al, 2022 ). According to a study, the effects of childhood maltreatment could last for decades and are strongly associated with the onset of mental disorders at an older age ( Macpherson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on theoretical deliberations implying an influence of maternal age (e.g., [ 67 , 68 ]), parity (e.g., [ 69 ]), academic degree (e.g., [ 70 , 71 ]), FOC, and depressive symptoms (e.g., [ 4 , 31 ]) on lifetime trauma, stress-related hair biomarkers, and CB-PTSS, these were controlled for as confounding variables [ 72 ]. Exposure to the COVID-19 pandemic did not affect CB-PTSS ( r s = −.02, p = .701), and was therefore not included in analyses with CB-PTSS as the dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…Social determinants of health are described as "conditions in the places where people live, learn, work, and play, that impact many health risks and outcomes" (1). The causal priority is ascribed to the environmental factors of childhood in considering the social gradient in mental health, a concept known as the "indirect selection of health services" hypothesis (2,3).…”
Section: Introductionmentioning
confidence: 99%